A Systematic Review of the Reported Proportions of Diagnoses for Dizziness and Vertigo. Issue 1 (January 2019) - Parker, Ian Gerard; Hartel, Gunter; Paratz, Jennifer; Choy, Nancy Low; Rahmann, Ann
Abstract : Objectives: To determine the typical proportions of diagnoses for patients presenting with dizziness or vertigo based on clinical speciality and to assess the change in proportions of diagnoses over time. Data Sources: Following PRISMA guidelines, systematic searches of PubMed and CINAHL databases and follow-up reference searches were performed for articles published in English up to October 2016. Study Selection: Analysis of searches yielded 42 studies meeting the criteria of case series of adult patients with dizziness and/or vertigo presenting to general practice, emergency departments or specialist outpatient clinics. Data Extraction: Data comprising demographics, diagnostic cases, and the total number of cases were recorded and independently tested, followed by a risk of bias analysis. Data Synthesis: Sample size weighted proportions expressed as percentages with confidence intervals were calculated and compared using χ 2 analysis and a reference proportion formed by the combination of Ear Nose and Throat and Neurotology case series published between 2010 and 2016. Analysis of diagnostic trends over time used Poisson regression with consideration for overdispersion. Conclusions: This systematic review of case series demonstrated significant differences in the proportions of diagnoses for patients presenting with dizziness or vertigo, depending on the specialty making the diagnosis. ENT proportions were dominated by BPPV, Psychogenic andMenière's disease diagnostic categories, whereas emergency proportions were dominated by Other, Cardiac, and Neurological categories. Analysis of case series proportions over time revealed increases in diagnoses such as Benign Paroxysmal Positional Vertigo and Vestibular Migraine, and a corresponding decrease in the diagnoses ofMenière's disease. Abstract : Supplemental Digital Content is available in the text